Oral History Interview with Barbara Blackdeer-Mackenzie by Tiffany Gerber - Blackdeer-Mackenzie, Barbara; Gerber, Tiffany (My University, 2009)
This interview is part of an oral history project conducted in honor of the 25th anniversary of the Women's Studies Program at the University of Wisconsin - Eau Claire.